The Reality Of Using The Internet By Faculty Members In The College Of Veterinary Medicine - Al-Qasim Green University - Hadi Jassim, Muhammad; Kadhim Hantoush, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the services provided by the online international information network and the possibility of employing its programs and its various applications and benefiting from the process of data collection for an educational academy through a survey sample of the views of professors from the denominator Green/University College of Veterinary Medicine to know the reality of use of the Internet and ways to invest service for the university education process. The research adopted the descriptive analysis method that is appropriate to the nature of this research, which is concerned with investigating opinions about the use of modern technologies on the Internet. The research sample consisted of 44 (one out of 75) faculty members at Al-Qasim Green University/College of Veterinary Medicine. The adoption of a questionnaire to gather information from the research sample and found the field study to the next most important results: The majority of respondents use the Internet on an ongoing basis for all that is new information in the field of jurisdiction and to keep abreast of scientific developments in the field of specialization, and a high percentage of the respondents see that the Internet is a very important research and scientific communication channel for a university professor. The problems of slow network speed and frequent interruptions in communication are among the obstacles that pose problems in the face of the research activity of professors on the Internet.